A new Jun amino-terminal kinase inhibitor, KRev-202, inhibits rat ischemic acute injury and the progression to renal fibrosis - Nikolic-Paterson, David J.; Tesch, Greg H.; Ozols, Elyce; Jarnagin, Kurt; Satoh, Yoshi; Webb, David R.; Squiers, Elizabeth; Grynberg, Keren; Ma, Frank Y. (Frontiers in Pharmacology, 2026)
IntroductionIschemia is an important cause of acute kidney injury (AKI). Ischemia-induced hypoxia rapidly induces activation of the Jun amino-terminal kinase (JNK) in tubular epithelial cells of the kidney, and blockade of this enzyme is protective in short-term animal models of renal ischemia. However, the clinical translation of this finding requires a water-soluble JNK inhibitor. This study investigated whether KRev-202, a soluble prodrug of the potent and selective JNK inhibitor CC930, can prevent ischemia-induced AKI and whether short-term inhibition of JNK can prevent AKI from transitioning to renal fibrosis.MethodsIn a rat model of bilateral renal ischemia/reperfusion injury (IRI), the animals received prophylactic treatment with KRev-202, the parent compound (CC-930), or a vehicle by oral gavage, starting 1 h prior to surgery.Results and DiscussionIn study 1, the animals were killed on day 1 after IRI to assess the AKI peak. Vehicle-treated animals exhibited a 4.5-fold increase in plasma creatinine levels, substantial tubular necrosis, increased tubular damage markers, and inflammation on day 1. Both KRev-202 and CC-930 treatment inhibited JNK activation, caused a 50% reduction in plasma creatinine levels, and substantially reduced tubular necrosis, tubular damage, and inflammation. In studies 2 and 3, treatments were administered from −1 h until day 4, and then the animals were killed on days 7 and 21, respectively. Compared to the vehicle group, a 4-day treatment with KRev-202 or CC-930 improved the recovery of tubular structure on day 7 and substantially reduced the development of renal fibrosis on day 21. Furthermore, KRev-202 treatment administered only during the first 24 h of IRI provided the same benefits as the 4-day treatment regimen, demonstrating the importance of early blockade of this pathway. In conclusion, KRev-202 is a new water-soluble JNK inhibitor with therapeutic potential for preventing ischemia-induced AKI.